A 3D tailored monolithic glass chip for stimulating and recording zebrafish neuronal activity with a commercial light sheet microscope - Schrödter, Dominika; Mozafari, Mohadeseh; Fichtner, Janine; von Trotha, Jakob William; Köster, Reinhard Wolfgang; Dietzel, Andreas (Frontiers in Lab on a Chip Technologies, 2024)
Microfluidic technology is unrivaled in its ability to apply soluble chemical stimuli with high spatiotemporal precision. Analogous, light-sheet microscopy is unmatched in its ability of low phototoxic but fast volumetric in vivo imaging with single cell resolution. Due to their optical translucency during the larval stages, zebrafish (Danio rerio) are an ideal model to combine both techniques; yet, thus far this required light-sheet microscopes, which were in most cases custom-built and adapted to the available softlithographic chip technology. Our aim was to use a commercial lightsheet microscope to illuminate a microfluidic chip from two opposite lateral directions and to record images with the detection objective placed orthogonally above the chip. Deep tissue penetration can be achieved by superimposing beams from opposite directions to form a single light sheet. But a microfluidic chip that allows a) targeted stimulus application in a closed microenvironment, b) interference-free incoupling of excitation light from two directions and c) outcoupling of fluorescence in the perpendicular direction through an optically perfect cover glass was not known until now. Here, we present a monolithic glass chip with the required plane-parallel sidewalls and cover slide closure at the top, constructed by advanced femtosecond laser ablation, thermal bonding and surface smoothing processes. In addition, the 3D shape of a fish fixator unit was tailored to match the body shape of a zebrafish larva to ensure stable positioning during whole-brain recording. With hydrodynamic focusing a targeted partial exposure of the larva's head to chemical stimuli and fast position switching (in less than 10 seconds) was possible. With the capabilities of this unique monolithic glass chip and its up-scalable wafer-level fabrication process, the new NeuroExaminer is prone to become an excellent addition to neurobiology laboratories already equipped with high-quality commercial light sheet microscopes.